2016
DOI: 10.1089/tmj.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Commercial Pedometers for Monitoring Slow Walking Speed Populations

Abstract: It was observed that all the evaluated devices have high error rates at 1 km/h and mixed error rates at 2 km/h, and at 3 km/h the error rates are the smallest of the three assessed speeds, with the OM and the FB having a slight overcount. These results show that research on pedometers' software and hardware should focus more on accurate step detection at slow walking speeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…Although patients operated for proximal femur fractures move differently and walk slowly compared to a young and healthy population [28], their physical activity could be measured reliably using a specific algorithm developed for this purpose [20]. Hereby, the very low activity levels found in this cohort was consistent with earlier findings [10,18,[29][30][31], although the absolute values were higher in this study caused by the recently adapted threshold [20].…”
Section: Discussionsupporting
confidence: 88%
“…Although patients operated for proximal femur fractures move differently and walk slowly compared to a young and healthy population [28], their physical activity could be measured reliably using a specific algorithm developed for this purpose [20]. Hereby, the very low activity levels found in this cohort was consistent with earlier findings [10,18,[29][30][31], although the absolute values were higher in this study caused by the recently adapted threshold [20].…”
Section: Discussionsupporting
confidence: 88%
“…In general, accuracy studies have reported counting errors in the step readings of such counters, particularly in cases of low walking speed,15–17 high body mass index18 and individuals with gait disorders and functional limitations 1319 20 Step counter accuracy has often been studied in healthy adults and under controlled conditions, for example, on a treadmill 1517 20–23 However, treadmill walking is not representative of normal walking.…”
Section: Introductionmentioning
confidence: 99%
“…They have been in use for many years, but pedometers are not accurate when used for activities that do not involve footfalls (such as swimming or upper body movements). Moreover, accuracy may be poor among specific populations, and among different models [31]. Accelerometers are technically more advanced than pedometers and being multi-axial can measure horizontal, lateral, and vertical movements.…”
Section: Physical Activity Monitoring and Assessmentmentioning
confidence: 99%